Escape Room Game Design Has Teaching Potential for Engaging With Misinformation Behaviors - Stephenson, Collin (Evidence Based Library and Information Practice, 2025)
A Review of: Cho, Y., Coward, C., Lackner, J., Windleharth, T. W., & Lee, J. H. (2023). The use of an escape room as an immersive learning environment for building resilience to misinformation. Journal of Librarianship and Information Science, 57(2), 524-538. https://doi.org/10.1177/09610006231208027 Objective – To evaluate the efficacy of game-based learning as a tool to teach misinformation recognition strategies, with an additional focus on cognitive bias, emotion, and attitudes related to misinformation. The authors also explore librarians’ responses to the use of the game as library educational programming to identify strengths and areas of concern in the game design process. Design – Mixed-methods user study combining participant survey data with inductive and deductive coding of qualitative data extracted from video recordings and open-ended questions. Setting – Washington State public libraries, primarily city and suburban locations. Subjects – 80 public library patrons and 6 public librarians in gameplay; 50 patrons additionally completed the optional survey. Methods – For this exploratory study, authors designed a misinformation escape room game based on interviews with librarians, college student input, and escape room developer collaboration. The authors recruited and trained public librarians to host the game and facilitate follow-up discussions, then recruited 80 participants via communication channels chosen by the public librarians, including newsletters, websites, and social media. The game was run 17 times across six locations. Game participation and discussions were recorded and transcribed. Following the game, participants were asked to complete a survey that included quantitative and qualitative responses, and librarians participated in a focus group after completing all of their game sessions. Researchers then coded the responses with both predefined and emergent codes. Main Results – Researchers found that participants were exposed to new misinformation techniques during the game, especially deepfake images and videos. Participants stated in the follow-up discussion that the use of misinformation created a sense of vulnerability, and they reflected on their individual responsibility regarding the spread of misinformation, including that once misinformation is shared, it cannot truly be unshared. As a result of the game, many participants highlighted the need for greater caution and critical thinking when engaging with information. Participants appreciated that the game was both fun and cooperative while affirming that it improved their awareness of misinformation techniques. Conclusion – The combination of immersive experience, collaborative play, and the post-game discussion led to better awareness of modern misinformation techniques and a willingness to reflect on the experience of engaging in misinformation. The post-game debrief is particularly important as it allows participants to form connections between the game and real-world misinformation experiences. Further research could pursue more conclusive evidence regarding patterns in misinformation experiences, or a longitudinal study could explore the game’s long-term effects on participants’ attitudes and behaviors.